2013
DOI: 10.1002/cncr.28453
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and enhanced chemosensitivity in experimental pancreatic cancers induced by noninvasive radiofrequency field treatment

Abstract: Background Patients with pancreatic adenocarcinoma (PDAC) have limited therapeutic options and poor response to the standard gemcitabine (GCB)-based chemotherapy. We investigated the feasibility of non-invasive short-wave RF electric fields to improve cytotoxic effect of GCB on PDAC cells and determined its mechanism of action. Methods Cytotoxicity of RF alone and in combination with GCB was studied in vitro on normal pancreatic HPDE cells and different PDAC cell lines by flow cytometry, and in vivo on ectop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 22 publications
3
38
0
Order By: Relevance
“…Increased levels of LC3B green fluorescent puncta were noticed only in cells exposed to the RF field, indicating an increased presence of autophagosomes in cells after RF exposure (Fig. ) and correlating with our previous studies in which we performed a thorough investigation of RF‐induced autophagy . Red fluorescence staining with Tom20 antibody designating mitochondria was similar in both treated and untreated cells.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Increased levels of LC3B green fluorescent puncta were noticed only in cells exposed to the RF field, indicating an increased presence of autophagosomes in cells after RF exposure (Fig. ) and correlating with our previous studies in which we performed a thorough investigation of RF‐induced autophagy . Red fluorescence staining with Tom20 antibody designating mitochondria was similar in both treated and untreated cells.…”
Section: Resultssupporting
confidence: 89%
“…Recent studies by other investigators have demonstrated that deprivation of ATP production can stimulate an autophagy mechanism in cells for alternative energy sources . In our previous studies, we were able to show that RF treatment of cancer cells was followed by induction of autophagy . Data obtained in the current study indicate that substantial reduction of oxygen consumption in RF‐treated cancer cells could be one of the initiating signals for autophagy activation, as seen by the increase in green LC3B puncta signals in Fig.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations